Perda de carga em reduções concêntricas de PVC - Oliveira, Francienne Gois [UNESP]; Resende, Paulo Rogério Nascimento; Barreto, Antonio Carlos; Seraphim, Odivaldo José [UNESP] (My University, 2011)
In the pumping pipelines the located load losses are very important since they have direct influence on hydraulic design of an irrigation system, especially regarding the concentric reducers used in the distribution lines. Hence this work was conducted in the Laboratório de Hidráulica do Centro Federal de Educação Tecnológica de Uberaba. We analyzed 03 concentric reducers PVC 75 x 50 mm, 50 mm and 35 x 35 x 1 "operating at different flow rates. The performance of the tests with the variation of flow in every situation possible to obtain equations to estimate the loss. The equation models presented a high setting, thus enabling the determination of the localized head loss in a situation closer to field reality. For the reduction of 75 x 50 x 35 mm and 50 mm at a flow rate 16.97 m³ h-1 the pressure drop reduction was obtained respectively 0.9263 and 2.7408 mca. To the reduction of 35 x 1 "at a flow rate of 6.02 m³ h-1 was obtained 2.9304 mca pressure drop reduction. The located losses produced by these reductions are relatively high and should be considered with great discretion in hydraulic design of the irrigation system.

Nas tubulações de recalque as perdas de carga localizadas são de suma importância, uma vez que têm influência direta no dimensionamento hidráulico em um sistema de irrigação, principalmente no que tange as reduções concêntricas utilizadas nas linhas de distribuição. Em função disso, realizou-se este trabalho no Laboratório de Hidráulica do Centro Federal de Educação Tecnológica de Uberaba. Foram analisadas 03 reduções concêntricas de PVC de 75 x 50 mm, 50 x 35 mm e 35 x 1”, operando com diferentes vazões. A realização dos ensaios com a variação da vazão em cada situação possibilitou a obtenção de equações para estimar a perda de carga. Os modelos de equação apresentaram altos coeficientes de ajuste, possibilitando a determinação da perda de carga localizada numa situação mais próxima da realidade de campo. Para as redução de 75 x 50 mm e 50 x 35 mm à uma vazão de 16,97 m³h-1 a perda de carga na redução obtida foi de respectivamente 0,9263 e 2,7408 m.c.a e para a redução de 35 x 1” à uma vazão de 6,02 m³h-1 obteve-se 2,9304 m.c.a de perda de carga na redução. As perdas de carga localizada produzidas por essas reduções são relativamente altas e devem ser consideradas com bastante critério no dimensionamento hidráulico do sistema de irrigação.
Load loss in concentric reductions of PVC
Keywords: Irrigation; Load loss; Connections; Irrigação; Perda de carga; Conexões